Adult-specific Reelin expression alters striatal neuronal organization: implications for neuropsychiatric disorders - Pardo, Mònica; Gregorio, Sara; Montalban, Enrica; Pujadas, Lluís; Elias-Tersa, Alba; Masachs, Núria; Vílchez-Acosta, Alba; Parent, Annabelle; Auladell, Carme; Girault, Jean-Antoine; Vila, Miquel; Nairn, Angus C.; et al. (Frontiers in Cellular Neuroscience, 2023)
In addition to neuronal migration, brain development and adult plasticity, the extracellular matrix protein Reelin has been extensively implicated in human psychiatric disorders such as schizophrenia, bipolar disorder and autism spectrum disorder. Moreover, heterozygous reeler mice exhibit features reminiscent of these disorders, while overexpression of Reelin protects against its manifestation. However, how Reelin influences the structure and circuits of the striatal complex, a key region for the above-mentioned disorders, is far from being understood, especially when altered Reelin expression levels are found at adult stages. In the present study, we took advantage of complementary conditional gain- and loss-of-function mouse models to investigate how Reelin levels may modify adult brain striatal structure and neuronal composition. Using immunohistochemical techniques, we determined that Reelin does not seem to influence the striatal patch and matrix organization (studied by µ-opioid receptor immunohistochemistry) nor the density of medium spiny neurons (MSNs, studied with DARPP-32). We show that overexpression of Reelin leads to increased numbers of striatal parvalbumin- and cholinergic-interneurons, and to a slight increase in tyrosine hydroxylase-positive projections. We conclude that increased Reelin levels might modulate the numbers of striatal interneurons and the density of the nigrostriatal dopaminergic projections, suggesting that these changes may be involved in the protection of Reelin against neuropsychiatric disorders.